Index of Microcirculatory Resistance Measured during Intracoronary Adenosine-Induced Hyperemia. (13th May 2020) - Santos-Pardo, Irene; Alström, Patrik; Witt, Nils
Abstract : Background . The index of microcirculatory resistance is an invasive measure of coronary microvascular function that has to be calculated during maximal hyperemia, classically achieved with intravenous adenosine (IV). The aim of this study was to evaluate the use of intracoronary (IC) adenosine for the calculation of IMR. Methods and Results . 31 patients with stable coronary artery disease were included in the study. Coronary pressure and thermodilution measurements were obtained at rest and during maximal hyperemia using a pressure-temperature sensor-tipped coronary guidewire. Duplicate measurements were performed using first IC and then IV adenosine. Dispersion of transit times was comparable for IC and IV adenosine. IMR values based on IC vs IV adenosine showed a high level of agreement and an intraclass correlation coefficient of 0.90. Applying an upper normal limit of 25, misclassification of IMR using IC adenosine was seen in just one patient in whom IC adenosine resulted in a lower value. A simplified procedure based on a single bolus dose of saline did not change the level of agreement or the rate of misclassification. Conclusions . We found an excellent agreement between IMR values measured during hyperemia induced by IC as compared to IV adenosine. The use of IC adenosine may facilitate invasive assessment of microvascular function and is potentially time- and cost-saving with less patient discomfort as compared to IV infusion. The trail is registered with NCT03369184 .